Relationship of RIC-3 gene rs1528133 polymorphism with varying degrees of body weight and eating behavior. - (:unkn) unknown (My University, 2012)
The aim of this study was to determine the allele frequencies of resistance to inhibitors of cholinesterase 3 homologue (RIC-3) gene rs1528133 polymorphism in overweight+obese+morbid obese and non-obese (non-OB) subjects. The effects of rs1528133 genotypes on anthropometric, diabetes and obesity related parameters, self-reported macronutrient intake and drugs were also evaluated. The study was performed on overweight+obese+morbid obese and non-obese subjects. RIC-3 gene rs1528133 genotypes were determined with qPCR. The RIC-3 rs1528133 genotype frequencies were respectively as 89.4% for homozygous wild type (A/A), 10.6% for heterozygous (A/C) genotypes in overweight+obese+morbid obese patients and 92.7% for A/A, 7.3% for A/C genotypes in non-OB subjects. The homozygous mutant genotype (C/C) was not detected in our study population. Genotype frequencies were not significantly different among study groups. Heterozygous genotype carriers for the rs1528133 polymorphism were found to prefer higher glycemic load, fat and protein diet content compared to homozygous wild type genotype carriers (p=0.0001). The frequency of rs1528133 heterozygous individuals (16.7%) using antihypertensive drugs was lower (p=0.045) in comparison to wild type genotype carriers (46.9%) in the whole study population. RIC-3 gene rs1528133 variation was not found to be effective over any analyzed obesity related parameter, but associated with higher glycemic load, protein and fat eating behavior and antihypertensive drug use. Copyright © 2012 Diabetes India. Published by Elsevier Ltd. All rights reserved.